Evaluation of L-PRF combined with deproteinized bovine bone mineral for early implant placement after maxillary sinus augmentation: A randomized clinical trial - Pichotano, Elton Carlos [UNESP]; de Molon, Rafael Scaf [UNESP]; de Souza, Ricardo Violante; Austin, Rupert S.; Marcantonio, Elcio [UNESP]; Zandim-Barcelos, Daniela Leal [UNESP] (Wiley, 2019)
Purpose: To investigate the effectiveness of adding leukocyte and platelet-rich fibrin (L-PRF) to deproteinized bovine bone mineral (DBBM) for early implant placement after maxillary sinus augmentation. Materials and Methods: Twelve patients requiring two-stage bilateral maxillary sinus augmentation were enrolled to the study. The elevated sinus cavities were randomly grafted with DBBM + L-PRF (test) or DBBM alone (control) in a split-mouth design. Implants were placed in the augmented sites after 4 months in the test group and 8 months in the control group. Bone biopsies were collected during implant placement for histomorphometric evaluation. Resonance frequency analysis was performed immediately after implant placement and at implant loading in both groups. Cone-beam computed tomography was obtained preoperatively and postoperatively for evaluation of graft volume changes. Results: Both procedures were effective for maxillary sinus augmentation. Cone-beam computed tomography analysis did not reveal differences in graft volume between test and control group at any of the evaluated time points (P >.05). Histological evaluation demonstrated increased percentage of newly formed bone for the test group (44.58% ± 13.9%) compared to the control group (30.02% ± 8.42%; P =.0087). The amount of residual graft in the control group was significantly higher (13.75% ± 9.99%) than in the test group (3.59 ± 4.22; P =.0111). Implant stability quotient (ISQ) immediately after implant placement was significantly higher in the control group (75.13 ± 5.69) compared to the test group (60.9 ± 9.35; P =.0003). The ISQ values at loading did not differ between the groups (P =.8587). Implant survival rate was 100% for both groups. Conclusion: The addition of L-PRF to the DBBM into the maxillary sinus allowed early implant placement (4 months) with increased new bone formation than DBBM alone after 8 months of healing.
Keywords: alveolar bone; bone substitutes; cone-beam computed tomography; dental implants; maxillary sinus; platelet-rich fibrin; sinus floor augmentation